Dynamic Optimization of Data Packet-based Communication for PLC Visual Monitoring - Changjiang Ju; Genke Yang; Yu-Wang Chen; Changchun Pan (Applied Sciences, 2019)
This paper presents a dynamic optimization solution for the data packet-based communication of programmable logic controller (PLC) visual monitoring, and the objective is to improve the communication efficiency between a supervisory computer and field PLCs in consideration of the network communication performance, such as network bandwidth, packet loss or retransmission rate, and human response delay. A nonlinear optimization model with constraints is formulated and solved analytically to obtain the minimized transmission time. Experimental results demonstrate that the proposed dynamic optimization can solve the practical industry problem in an efficient and effective manner, and it can provide useful guidance for the data packet-based communication setting of networked control systems.